2019
DOI: 10.3390/md17110629
|View full text |Cite
|
Sign up to set email alerts
|

Unique Aggregation of Sterigmatocystin in Water Yields Strong and Specific Circular Dichroism Response Allowing Highly Sensitive and Selective Monitoring of Bio-Relevant Interactions

Abstract: We demonstrated the hitherto unknown property of the mycotoxin sterigmatocystin (STC) to provide homogeneous solutions in aqueous medium by forming a unique aggregate type (not formed by analogous aflatoxins), characterized by exceptionally strong circular dichroism (CD) bands in the 300–400 nm range. Results showed that these CD bands do not originate from intrinsic STC chirality but are a specific property of a peculiar aggregation process similar to psi-DNA CD response. Transmission electron microscopy (TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 57 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…The acute oral toxicity of STC is relatively low and related to liver and kidney damage; chronic respiratory exposure of Wistar rats to STC‐producing Aspergilli provoked lesions in the lung and pleura and lung and endocrine organs tumor development 45 . Additionally, a recent study revealed that STC possesses unique aggregation properties in water, yielding a strong and specific circular dichroism spectrum which showed that STC interacts with DNA strongly and non‐covalently, with likely toxic effects which is contrary to requiring prior enzymatic epoxidation 46 . A few studies on human lung cell cultures revealed the cytotoxic and genotoxic potential of both STC and 5‐MET‐STC as well as the cytotoxicity of STC‐producing Aspergilli ( Versicolores ) 4,34,43,47,48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute oral toxicity of STC is relatively low and related to liver and kidney damage; chronic respiratory exposure of Wistar rats to STC‐producing Aspergilli provoked lesions in the lung and pleura and lung and endocrine organs tumor development 45 . Additionally, a recent study revealed that STC possesses unique aggregation properties in water, yielding a strong and specific circular dichroism spectrum which showed that STC interacts with DNA strongly and non‐covalently, with likely toxic effects which is contrary to requiring prior enzymatic epoxidation 46 . A few studies on human lung cell cultures revealed the cytotoxic and genotoxic potential of both STC and 5‐MET‐STC as well as the cytotoxicity of STC‐producing Aspergilli ( Versicolores ) 4,34,43,47,48 .…”
Section: Resultsmentioning
confidence: 99%
“…45 Additionally, a recent study revealed that STC possesses unique aggregation properties in water, yielding a strong and specific circular dichroism spectrum which showed that STC interacts with DNA strongly and non-covalently, with likely toxic effects which is contrary to requiring prior enzymatic epoxidation. 46 A few studies on human lung cell cultures revealed the cytotoxic and genotoxic potential of both STC and 5-MET-STC as well as the cytotoxicity of STC-producing Aspergilli (Versicolores). 4,34,43,47,48 Altogether, we emphasize the health threats to inhabitants of post-flooded dwellings posed by indoor mold contamination and inhalation of STC and 5-MET-STC.…”
Section: A Pepii and A Protuberus Produced Stc But Not 5-met-stc mentioning
confidence: 99%
“…This may be explained by the additional methoxy group, an electron-donating group that activates the electrophilic hydroxyl group of 5-M-STC and thus may improve the bioavailability of 5-M-STC. Additionally, the lower cytotoxic potential of STC in comparison to 5-M-STC could be attributed to STC’s unique aggregation properties in water at concentrations between 5 and 10 μM, yielding a strong and specific circular dichroism spectrum [ 30 ]. Increasing the concentration of STC also increases the aggregation process, which in turn could decrease cell bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…In porcine primary tracheal epithelial cells treated with STC (50 μM), CYP enzymes produced a reactive STC metabolite [ 18 ], which may interact with DNA, leading to DNA single-strand breaks. On the other hand, a recent study revealed that STC at concentrations between 5 and 10 μM possesses unique aggregation properties in water, yielding a strong and specific circular dichroism spectrum [ 34 ]. Data showed that STC non-covalently interacts with DNA, most probably by intercalation between base pairs, which may result in DNA double-strand breaks [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a recent study revealed that STC at concentrations between 5 and 10 μM possesses unique aggregation properties in water, yielding a strong and specific circular dichroism spectrum [ 34 ]. Data showed that STC non-covalently interacts with DNA, most probably by intercalation between base pairs, which may result in DNA double-strand breaks [ 34 ]. We can only speculate whether both mechanisms may be in action, depending on the bioavailable concentration of STC and CYP activity.…”
Section: Discussionmentioning
confidence: 99%